2020
DOI: 10.1111/pirs.12482
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth through entrepreneurship: Determinants of self‐employed income across regional economies

Abstract: Knowledge of the determinants of self-employment incomeis critical to entrepreneurial development strategies if the development goal is to increase incomes not just employment. Using American Community Survey data, unconditional quantile regression is used to investigate differences in the relationship between entrepreneurial income and an array of individual, industry, and regional characteristics across the self-employment income distribution. Personal attributes, such as education, race, age, and gender, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…Although some empirical studies revealed a negative association between self-employment and income growth (Acs et al, 1994) (Barros & Pereira, 2008, others confirmed that selfemployment has positive impacts not only on income growth (Carpenter & Loveridge, 2017) (González-Sánchez et al, 2020 but also poverty reduction (Goetz et al, 2012), and regional development (Matejovsky et al, 2014). The factors that may cause uncorrelated motion between self-employment and income growth are, e.g., geographic location and education, race, age, and gender (Willis et al, 2020).…”
Section: An Association Between Women Self-employment and Economic Growthmentioning
confidence: 98%
“…Although some empirical studies revealed a negative association between self-employment and income growth (Acs et al, 1994) (Barros & Pereira, 2008, others confirmed that selfemployment has positive impacts not only on income growth (Carpenter & Loveridge, 2017) (González-Sánchez et al, 2020 but also poverty reduction (Goetz et al, 2012), and regional development (Matejovsky et al, 2014). The factors that may cause uncorrelated motion between self-employment and income growth are, e.g., geographic location and education, race, age, and gender (Willis et al, 2020).…”
Section: An Association Between Women Self-employment and Economic Growthmentioning
confidence: 98%
“…Most entrepreneurs choose and stay in their respective businesses even though they have low earnings than in paid employment (Hamilton, 2000). Research studies further reported that it depends on various factors, that is, the individual and nature of the local economies and resource availability (Willis et al, 2019). Some scholars presented a reverse picture of this relationship, particularly in the context of emerging economies.…”
Section: Entrepreneurship and Economic Growthmentioning
confidence: 99%
“…The employees whose wages are deprived of economic reason will not be inclined to take any action to improve their labor performance, i.e. they will neither make more efforts in the work here and now, nor spend time, energy and resources on professional self-development [10]. The principle 'each gains according to his needs', no matter how attractive it might be from a humanistic point of view, in no way stimulates the realization of the principle 'each gives according to his abilities' [11].…”
Section: B Grp Per Capita ↔ Per Capita Income and Grp Per One Employed In The Economy ↔ Average Monthly Nominal Wagementioning
confidence: 99%